PENGEMBANGAN EKOWISATA SEBAGAI PENDEKATAN PENGELOLAAN SUMBERDAYA PESISIR BERKELANJUTAN - Mukaryanti, Mukaryanti (Jurnal Teknologi Lingkungan, 2005)
Ecotourism has been chosen as an approach to integrate conservation and economic development in Blendung Village, one of coastal villages in the north coast of Pemalang District. Most of its community depend their livelihood on fish ponds and jasmine plantation. The combination of fish ponds, jasmine plantation and mangrove conservation is expected to be tourist attraction, which ables to enhance the prosperity of local community as well as to recover the function of mangrove as a means for coastal protection that has been lost recently. In order to prepare Blendung Village as a tourist destination, an environmentally- sound tourism area plan was created, and the skill of local community to manage the acitities was developed. The main challenge in the development of ecotourism in Blendung Village is how to empower local community as well as local government, thereby all of those local potentials could be developed, which in turn a sustainable coastal zone could be achieved.